2000
DOI: 10.4049/jimmunol.164.12.6096
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: T Cell-Mediated Pathology in Murine Lyme Borreliosis

Abstract: Even in the absence of an appropriate model or direct evidence, T cells have been hypothesized to exacerbate the manifestations of Lyme disease. To define definitely the role of T cells in Lyme disease, the course of disease in immunocompetent and B cell-deficient mice was compared. By 8 wk postinoculation, immunocompetent mice resolved both carditis and arthritis, whereas foci of myocarditis and severe destructive arthritis characterized disease of B cell-deficient mice. Cell transfer experiments using infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 23 publications
2
55
0
Order By: Relevance
“…Cell transfer experiments by these investigators showed that CD4 ϩ T cells were responsible for the aggravated carditis. 21 However, one can also speculate that the greater inflammation in Igh6 Ϫ/Ϫ mice was attributable to the loss of some regulatory effect of B cells on T cells. Unlike the Lyme disease model, we observed worsening of the disease across all of the clinical measures, including arthritis, conjunctivitis, ruffled fur, vestibular dysfunction, and weight loss (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell transfer experiments by these investigators showed that CD4 ϩ T cells were responsible for the aggravated carditis. 21 However, one can also speculate that the greater inflammation in Igh6 Ϫ/Ϫ mice was attributable to the loss of some regulatory effect of B cells on T cells. Unlike the Lyme disease model, we observed worsening of the disease across all of the clinical measures, including arthritis, conjunctivitis, ruffled fur, vestibular dysfunction, and weight loss (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which T cells may have exacerbated disease is by dampening the surge in IL-10 production by the innate immune system in response to rising pathogen loads, as seen in the Rag1 Ϫ/Ϫ mice. In the B. burgdorferi murine model of Lyme disease, McKisic and colleagues 21 found evidence that the presence of ␥␦ T cells worsens carditis but not arthritis. Cell transfer experiments by these investigators showed that CD4 ϩ T cells were responsible for the aggravated carditis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Iliopoulou et al (21) reported that C57BL/6 mice deficient for CD28-mediated costimulation develop chronic joint inflammation and have increased titers of anti-OspA antibodies. However, the results from another study (22), relying on adoptive transfer of cells to immune deficient mice, suggested that CD4 ϩ T cells, in the absence of B lymphocytes, exacerbate arthritis and carditis. Last, with regard to the regulation of inflammation and disease resolution, a recent study has shown that T-independent antibodies from marginal zone (MZ) B cells have a major role, because their depletion leads to reduced B. burgdorferi-specific IgM and IgG titers, enhanced pathogen burden and more severe arthritis (23).…”
mentioning
confidence: 97%
“…For this animal model, disease is believed to reflect the innate immune response to spirochetes because histopathology reveals mainly neutrophils and macrophages within inflamed joints and hearts, respectively, and arises in the absence of adaptive immunity (11,26,33,35). B. burgdorferi infections of severe combined immunodeficiency (SCID) and rag-deficient mice, which lack both T and B cells (11,26,33,35 …”
mentioning
confidence: 99%
“…For this animal model, disease is believed to reflect the innate immune response to spirochetes because histopathology reveals mainly neutrophils and macrophages within inflamed joints and hearts, respectively, and arises in the absence of adaptive immunity (11,26,33,35). B. burgdorferi infections of severe combined immunodeficiency (SCID) and rag-deficient mice, which lack both T and B cells (11,26,33,35), or of mice deficient in B cells alone (13,26) result in higher pathogen burdens but do not have altered disease incidence. In contrast to the disease in immunocompetent mice, however, neither carditis nor arthritis regresses in mice that are deficient in B and T cells (11).…”
mentioning
confidence: 99%